La política sanitaria durante el régimen de Porfirio Díaz, su aplicación en el Distrito Sur de la Baja California - Rivas Hernández, José Ignacio (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
This work has as purpose rebuild the process of implementation of health policy of Porfirio Diaz’s regime in a peripheral region of the country, as the Distrito Sur of Baja California was in the past. In the first section it is analyzed both sides, the police and the goodmunicipal government which was issued during the XIX century, whose main purpose was to regulate the order, security, ornament, comfort and knowledge. These sides were changing as the economy and demography changed too, this condition was the one which charge higher boom during the Porfirian regime. In the second section, it is described the epidemics that disturbed the district population, such as: smallpox, yellow fever and bubonic plague. It is analyzed the factors which led to the development of these diseases as well as the question if the fact of the development of these illnesses affected the demographic growth as well as the productive activities at the time. In the third section it is studied the hospital services creation, it is started by the explication of the health care system before the first hospitals appeared in the zone. Then, it is analyzed the factors which led to institute the “Salvatierra hospital” in La Paz as well as the “El Boleo hospital” in Santa Rosalia. It is explained how these institutions did not have the same profile, because their characteristics differed as to the sources of resources for their sustenance, infrastructure and equipment, internal organization and type of diseases they were dealing with.

Este trabajo tiene como propósito reconstruir el proceso de aplicación de la política sanitaria del régimen de Porfirio Díaz en una región periférica del país, como lo fue el Distrito Sur de la Baja California. En el primer apartado se analizan los bandos de policía y buen gobierno municipales que se expidieron durante el siglo XIX, los cuales tenían como objetivo reglamentar el orden, la seguridad, el ornato, la comodidad y la salubridad. Estos bandos se fueron transformando a la par que se daba el crecimiento económico y demográfico, condición que cobró mayor auge durante el régimen porfiriano. En el segundo apartado se describen las epidemias que inquietaron a los habitantes del distrito, como la viruela, la fiebre amarilla y la peste bubónica. Se revisan cuáles fueron los factores principales que propiciaron el desarrollo de estas enfermedades y sí afectaron el crecimiento demográfico y las actividades productivas. En el tercer apartado se estudia la creación de los servicios hospitalarios, se inicia con la explicación del sistema de atención médica antes de que aparecieran los primeros hospitales. Enseguida se consideran los factores que llevaron a instituir en el puerto de La Paz el Hospital Salvatierra y en el de Santa Rosalía el hospital El Boleo. Se explica cómo estas instituciones no tuvieron el mismo perfil, pues sus rasgos diferían en cuanto a las fuentes de recursos para su sostenimiento, infraestructura y equipamiento, organización interna y tipo de enfermedades que trataban.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2139; info:eu-repo/classification/cti/4; IIH-D-2017-1785; Epidemias; Servicios hospitalarios; Distrito sur se la Baja California